ARCHAEOLOGICAL RELICS OF DAK R’LAP DISTRICT, DAK NONG PROVINCE, IN THE REGIONAL PREHISTORIC CONTEXT - Thanh Vuong Nguyen (Tạp chí Khoa học Đại học Đà Lạt, 2023)
This article systematizes the documentation of prehistoric archaeological relics and artifacts from Dak R’lap District, Dak Nong Province. The article also presents the results of investigations, new discoveries, and surveys conducted by the author together with archaeologists from the Vietnam Institute of Archaeology. The author outlines the characteristics, properties, and dates of relics and artifacts; describes the locations, roles, and close relationship of relics and artifacts discovered in Dak R’lap District with the prehistory of Dak Nong in particular and the Central Highlands and Southeast in general. This research provides more data for the construction of prehistoric archaeological maps; facilitates researching, compiling, and educating on local history; and promotes sustainable cultural tourism development in Dak Nong Province in general.